GEOLOGI DAN HIDROGEOLOGI DAERAH HAMBALANG DAN SEKITARNYA KABUPATEN BOGOR, PROVINSI JAWA BARAT - FAJARUDIN KUSUMA , ALAM
This research was conducted to study geologic and hydrogeologic conditions in Hambalang area, Bogor Regency, West Java. The geologic conditions studied are geomorphology, stratigraphy, geological structure, geological history, and hydrogeology, covering the distribution of aquifers, groundwater flow patterns and its quality. Geographically, the research area is a located in Citeureup, Babakan Madang, and Klapanunggal Districts. This area is located in UTM coordinates of 708500 – 714000 mE and 9270000 – 9280000 mS (48S zone) with the total area of 55 km2. Based on landform classification, the research are is divided into seven geomorphological units. Those units are Citeureup Alluvial Plain, Siangin Karst Hills, Citeureup Faulted Folded Hills, G. Hambalang Pyroclastic Flow Ridge, Puncak II Anticline Ridge, Babakan Madang Intrusion Hill, and Babakan Madang Lava Flow Ridge. Stratigraphically, the research area can be divided into seven non-formal lithological units formed in Middle Miocene - Holocene epoch. Those units, from oldest to youngest, are Claystone unit, Sandstone-Claystone unit, Limestone unit, Andesite Intrusion unit, Andecite Lava unit, Pyroclastic Breccia unit, and Alluvial unit. Geological structures in the research area are product of compressional deformation regime, formed in Plio-Pleistocene epoch. Those structures are thrust faults, anticlines, syncline, and a strike-slip fault. Aquifers in the research area are sandstone, limestone, fractures in claystone, and result of weathering as unconfined aquifers and confined aquifers. Groundwater generally flows from south to north. The springs which are found in the research area are cold springs as depression springs, contact springs, fracture springs, and karst spring, as well as hot springs that are a manifestation of geothermal system. In 41 cold springs and 31 groundwater wells, TDS ranges from 16,1 to 580 mg/l, whereas in three hot spring, TDS ranges from 936 to 3370 mg/l.